A new paradigm of development as a modern challenge in agriculture = Nowy paradygmat rozwoju jako współczesne wyzwanie rolnictwa - Czyżewski, Andrzej; Czyżewski, Bazyli (Zielona Góra: Faculty of Economics and Management Press)
The authors of the paper propose a thesis of a necessary change of an industrial development paradigm of agriculture to a socially sustainable one. They present the mechanism of functioning of the first one proving that by stimulating the growth of production of agricultural raw materials it leads to a decreasing marginal productivity and, as a result, to lower incomes of farmers in the conditions of incomplete internalisation of costs.
Keywords: rolnictwo; paradygmat rozwoju rolnictwa; dobrostan środowiska; rolnictwo jako dobro publiczne; współczesna renta gruntowa; agriculture; agricultural development; agriculture as a public good; modern land rent